(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
During ontogenesis, plants are exposed to various stress factors of biotic and abiotic nature. The nucleus and mitochondria are the most sensitive to ionizing radiation cell elements of all living organisms. The effect of ionizing radiation on the electrokinetic potential of isolated nuclei of wheat seedlings was studied, which allows us to judge the changes in the magnitude of the surface charge and its role in the functioning of the cellular nuclei. Changes were obtained in the values of the electrokinetic potential in isolated seedlings of irradiated seeds in a electric field. As a result of chain reactions, ionizing radiation changes the content of nuclear fractions, which in turn leads to a decrease in the surface charge and a decrease in the electromobility of nuclei.